Synthesis, Molecular Docking and Antitumor Activity of New Dithiazoles. (14th September 2021) - Farghaly, Thoraya A.; El-Metwaly, Nashwa; Al-Soliemy, Amerah M.; Katouah, Hanadi A.; Muhammad, Zeinab A.; Sabour, Rehab
Abstract: Natural compounds including bis -heterocyclic moieties displayed several applications in pharmaceutical, agrochemical, and industrial fields. Di-thiazoles are effective core of several anticancer drugs such as bleomycin. Derived from importance of di-thiazoles, herein, we synthesized novel series of di-thiazoles from condensation reaction of thiazole thiosemicarbazone derivative with α-haloketones. Physical features and chemical structures of new compounds formed were discussed and assured based on their spectral and conformational analysis. The cytotoxic potency of newly synthesized thiazole derivatives against colon (HCT-116) and hepatocellular (HepG2) carcinoma-cell lines was determined by MTT assay. Compounds 7a, 9a, 9c, and 9e revealed marked anticancer activity especially against (HCT-116). Molecular docking study was executed over chosen compounds referring to expected promising features against LDH-5, which appeared agree with biological results. This study was utilized to predict prior binding-efficiency of active thiazole compounds.